PSYCHOLOGICAL MANIFESTATIONS OF PROFESSIONAL MARGINALITY OF FUTURE SOCIAL WELFARE PROFESSIONALS - Blynova, Olena; Kisil, Zoryana; Tkach, Tamara; Semenova, Nataliia; Semenov, Oleksandr; Kaminska, Svitlana; Popovych, Ihor (Revista Inclusiones, 2020)
The purpose is to examine psychological manifestations of professional marginality and determine if future social welfare professionals have its structural components. Professional marginality is considered as a connection disruption in the system “person – profession – society”. The study establishes that the main factors of the formation of professional marginality are socially determined, professionally determined and personality factors. Factor analysis determines four models of the profession: 1) Awareness of one’s professional efficiency (competence, knowledge and skills) (“Personal model of the profession” (23.51%); the sub-system “person and profession”); 2) Awareness of social significance of the profession (“Social model of the profession” (18.31%); the sub-system “profession and society”); 3) Awareness of oneself as an in demand professional (“Individual model of the profession” (9.39%); the sub-system “professional and society”); 4) Lack of significant correlations with the indexes of professional identity / professional marginality and demand for the profession, the domination of extraversion and neuroticism (“Communicative model of the profession” (7.46%); it partly reflects the sub-system “profession and society”).